Application Of Restorative Justice To Settlement Criminal Acts Of Persecution - Afandi, Yozza; Haniyah, Haniyah; Hernintyas, Tuti (Fakultas Hukum Dehasen, 2025)
This study aims to analyze the application of restorative justice to perpetrators of persecution crimes. Restorative justice is an approach concept with the main focus on restoring relationships between parties (perpetrators and victims) and the community. The main goal of solving problems with this approach is to maintain a harmonious relationship balance, by mediating and restoring the relationship and reimbursing the losses caused, This research is a normative research with a legal approach, this research is very important to do considering that cases of persecution often occur among the community, while the application of criminal sanctions is felt to be ineffective, The results of the study show that in cases of persecution whose settlement uses a restorative justice approach, providing a fair and effective solution, providing benefits to both the victim (victim recovery), the perpetrator or the community, meaning that the settlement of the case is completed faster and there is a restoration of the relationship between the victim and the perpetrator in conducive circumstances in community social relations in addition to reducing the overloaded burden capacity of the court and correctional institutions. The need for restorative justice arrangements so that it can run optimally in resolving the crime of persecution.